The Effect of The Plyometric Training Program on Sportive Performance Parameters in Young Soccer Players - Önder Dağlıoğlu; Tahsin İnce (Türk Spor ve Egzersiz Dergisi)
The studies that aim to bring together the strength and the speed of movement are called plyometric trainings. Our aim in this study is to be able to show the effect of plyometric training program on sportive performance parameters in young soccer players and to make recommendations for coaches and sportsmen on sportive training and training planning from this point. Twenty-four male soccer players aged 17-22 making regular soccer training participated in the study. Two different groups were formed as experimental and control groups and a plyometric training program was applied to the experimental group for 3 days a week for 8 weeks. Both groups continued their normal soccer training. Height, weight, body mass index (BMI), body fat percentage (BFP), aerobic capacity (VO2max), anaerobic capacity, speed and flexibility were measured before and after training. The trainings known as drop jump, box jump, squat jump, split squat jump, overhead slam and plyometric push-up were applied to the plyometric training group. Vertical jump test was used for anaerobic capacity measurement. Flexibility test (Sit and Reach test) and speed test (30 m) were applied. For statistical analysis, Paired Sample t-test was used in group comparisons and Independent Sample t-test was used for intergroup comparisons. BFP, anaerobic capacity, VO2max, speed and elasticity values ​​were found to be significant after the plyometric training program of the experimental group (p lt;0.05). BFP and VO2max values ​​of the control group were significant (p lt;0.05). When the groups were compared, anaerobic capacity, speed and flexibility values were found to be significant in favor of the experimental group (p lt;0.05). There was no significant difference in weight, BMI, BFP and VO2max values ​​(p gt;0.05). As a result of our research, the plyometric training program applied to young soccer players is considered to have a positive effect on sportive performance parameters. It can be said that regular and programmed plyometric training improves sportive performance positively.